SNORA37/CMTR1/ELAVL1 feedback loop drives gastric cancer progression via facilitating CD44 alternative splicing - Banghe Bao; Minxiu Tian; Xiaojing Wang; Chunhui Yang; Jiaying Qu; Shunchen Zhou; Yang Cheng; Qiangsong Tong; Liduan Zheng (Journal of Experimental & Clinical Cancer Research)
Abstract Background Emerging evidence shows that small nucleolar RNA (snoRNA), a type of highly conserved non-coding RNA, is involved in tumorigenesis and aggressiveness. However, the roles of snoRNAs in regulating alternative splicing crucial for cancer progression remain elusive. Methods High-throughput RNA sequencing and comprehensive analysis were performed to identify crucial snoRNAs and downstream alternative splicing events. Biotin-labeled RNA pull-down, mass spectrometry, cross-linking RNA immunoprecipitation, and in vitro binding assays were applied to explore interaction of snoRNAs with protein partners. Alternative splicing and gene expression was observed by real-time quantitative RT-PCR and western blot assays. In vitro and in vivo studies were performed to investigate biological effects of snoRNAs and their protein partners in gastric cancer. Survival analysis was undertaken by using Kaplan-Meier method and log-rank test. Results SNORA37 was identified as an up-regulated snoRNA essential for tumorigenesis and aggressiveness of gastric cancer. Gain- and loss-of-function studies indicated that SNORA37 promoted the growth, invasion, and metastasis of gastric cancer cells in vitro and in vivo. Mechanistically, as an ELAV like RNA binding protein 1 (ELAVL1)-generated snoRNA, SNORA37 directly bound to cap methyltransferase 1 (CMTR1) to facilitate its interaction with ELAVL1, resulting in nuclear retention and activity of ELAVL1 in regulating alternative splicing of CD44. Rescue studies revealed that SNORA37 exerted oncogenic roles in gastric cancer progression via facilitating CMTR1-ELAVL1 interaction. In clinical gastric cancer cases, high levels of SNORA37, CMTR1, ELAVL1, or CD44 were associated with shorter survival and poor outcomes of patients. Conclusions These results indicated that SNORA37/CMTR1/ELAVL1 feedback loop drives gastric cancer progression via facilitating CD44 alternative splicing.